ABC of organic livestock husbandry - Kaswan, Sandeep; Mukherjee, Joydip (Indian Farming, 2015)
Organic farming has great scope for expansion in rainfed dryland agricultural regions (about 65% of the agricultural land), where green revolution technologies have failed to boost crop and livestock productivity. Organic farming indicates a selfsustaining and persistent agroecosystem in good balance. As livestock rearing under organic conditions has great benefits to sustainable agricultural system along with economic benefits, organic livestock husbandry can become boon to thousands of rural families if certified and utilized efficiently.